Pengaruh Capital Structure, Firm Size Dan Liquidity Terhadap Financial Performance - Meiliana, Jonnardi (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to obtain empirical evidence about the effects of capital structure, firm size and liquidity on financial performance in manufacturing industries listed in Indonesian Stock Exchange during the period of 2014-2018. This research used 64 samples of manufacturing companies that have been previously selected using purposive sampling method. Secondary data was used in the form of financial information from the financial statements and annual reports. This research data was processed using EViews 10. The result of this research shows that capital structure and firm size has a significant effect on financial performance, while liquidity do not have a significant effect on financial performance. Suggestions for the next study is to add another independent variables to strengthen the ability of independent variables in explaining the dependent variable.